Production of high-yielding and local varieties of aman paddy in Mymensingh : an economic analysis - Murshed, Sayed Md. Munzur (Production economics and farm management research report, 1976)
Reportage of findings contained in three M.Sc. theses submitted to the Dept. of Agricultural Economics, Bangladesh Agricultural University.